AI And Machine Learning In Islamic Guidance: Opportunities, Ethical Considerations, And Future Directions - Arif, Muhammad; Irfan, Sadia; Rhaman Shaoan, Md Mirajur; Ali, Wazir (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2024)
The rapid advancement of Artificial Intelligence (AI) offers new possibilities for enhancing counseling practices, including Islamic counseling, which combines psychological support with spiritual guidance. However, the integration of AI into this field raises significant ethical concerns. This study explores the ethical implications of AI in Islamic counseling through interviews with 10 Islamic scholars in Pakistan. The research employs Ethical AI Decision-Making and Islamic Counseling Ethics as theoretical frameworks to examine the potential benefits and limitations of AI in this context. The findings indicate that while AI can improve access to counseling services, particularly in underserved areas, it cannot replace the empathy, personalized care, and spiritual insight essential to Islamic counseling. Scholars emphasize that AI systems must align with Islamic ethical principles, ensuring confidentiality, fairness, and cultural sensitivity. AI should be viewed as a complementary tool rather than a replacement for human counselors, offering support in areas such as preliminary assessments or information delivery. The study contributes to the ongoing discourse on the intersection of AI and religious ethics, providing a foundation for future research on developing AI systems that are both technologically effective and ethically sound.